How to fight long-term unemployment: Lessons from Germany - Alexander Spermann (IZA Journal of Labor Policy, 2015)
The number of long-term unemployed in Germany has stagnated at around one million for several years. Despite excellent labour market conditions, the long-term unemployment rate is well above the OECD average. Therefore, the "carrot and stick" principle of Hartz reforms is in clear need of further development. The author proposes an overall concept for preventing and reducing long-term unemployment and long-term basic income receipt. An important element is an activation strategy for the long-term unemployed and long-term basic income recipients that implies interim target setting and requires more and better trained case managers in the job centres.
Keywords: J31; J38; 330; Long-term unemployment; Long-term basic income receipt; Germany; Training programmes; Active labor market policy; Activation